Problem of the person and society in the Arab prose (the first half of the XX century) - Koptileuova, D Т (Journal of Oriental Studies, 2016)
In the article the problem of mutual relations is examined between a man and society in works of the Arabic writers of the first half of the twentieth century. Where writers come forward for human rights, right on life, happiness, regardless of social origin. Also talked about rich in content and instructive senses of the examined works.